Unscrupulous marketing of snake bite antivenoms in Africa and Papua New Guinea: choosing the right product--'what's in a name?'. - Warrell, D (2008)
Snake bite envenoming, mainly caused by the saw-scaled or carpet viper (Echis ocellatus), is a neglected disease of West Africa. Specific antivenoms can save life and limb but, for various reasons, supply of these essential drugs to Africa has dwindled to less than 2% of estimated requirements. Other problems include maldistribution, inadequate conservation and inappropriate clinical use of antivenoms. In the face of this crisis, several promising new antivenoms have been developed. However, some dangerously inappropriate products of Indian origin are being marketed by unscrupulous manufacturers or distributors in Africa and Papua New Guinea, with disastrous results. A major source of confusion is labelling antivenom with ambiguous snake names that fail to distinguish the Asian species whose venoms are used in their production from the local snakes whose venoms are antigenically dissimilar.